CONSUMER DEPENDENCE ON SMART PHONES: THE EFFECT OF SOCIAL NEEDS, SOCIAL INFLUENCE AND CONVENIENCE IN SURABAYA - Steven Steven (Perpustakaan Universitas Surabaya, 2018)
This research aims to examine the affects of social needs, social influence and convenience to customers’ dependence on smart phone. This quantitative and causal type research uses questionnaires for one-site survey. Purposive sampling method was used. The sample consisted of 200 respondents whose age is 21 years old above, have owned and used smart phone in Surabaya at least last two years. The result were analyzed through descriptive statistics using SPSS 18.0 and LISREL 8.0 The result was found that there is a positive impact of social needs toward dependence on smart phone. There is a positive impact of social influence toward dependence on smart phone. Furthermore, there is also positive impact of convenience toward dependence on smart phone. However, the result shows no significant impact of dependence on smart phone toward purchase behavior.